PREDIKSI ARAH PENCEMARAN AIRTANAH AKIBAT TEMPAT PEMBUANGAN SAMPAH AKHIR DI DAERAH SARIMUKTI DAN SEKITARNYA KABUPATEN BANDUNG BARAT, PROVINSI JAWA BARAT - -, Bombom R. Suganda, T.; -, Yan W. M. Iskandarsyah; -, M. Sapari Dwi Hadian, (Bulletin of Scientific Contribution, 2012)
Geomorphology of the study area consists of rolling hills with slopes relief of moderate to rough. Slope toward south and southeast. The landfill site of Sarimukti are on steep hillsides, 16-25% slope, flanked by a ridge and ridge Sarimukti Margaluyu. What the study is about 100-400 meters from the highway west Rajamandala-Bojongmekar, Cipatat, West Bandung. Drainage pattern in this area is dendrito-parallel. Volcanic sediments underlying the landfill site of Sarimukti is lapili-tuff lithologies of Cibeureum Formation. This rock unit has a thickness of up to approximately 28 meters, consists of sandy tuff rock-gravelly (lapilli) and results of its wheatering, ie clayey-silt. Mixing the components in the form of lapili fragments. Based on hydrogeology, Sarimukti landfill and surrounding area has two aquifer systems, which are composed by rock aquifer sandy tuff, clayey-silt soils at the top of the unsaturated zone (aquifer was depressed / free) and aquifer half depressed / half-free, which has silty clay layer on the top of which belong to the layer aquitard. In this area the clayey silt soil hydraulic conductivity value is 10-3 cm / sec, while the sandy tuff rock layers at the bottom has a hydraulic conductivity of 10-2 cm / sec. Based on the topographic contour map and analysis estimated that the flow of groundwater in the area of landfill site Sarimukti and surrounding consists of four flow direction, the direction relative to the southeastern slope (hydraulic gradient) + 20-40%, towards the east with a slope of +10%, relative southwestern direction with a slope of + 10-20%, and the south with a slope of + 10%. Groundwater contamination that occurred in Sarimukti trend indicated by a pattern of chloride and bicarbonate ion plume to the southeast. The pattern of the spread of contamination is influenced by the direction of the slope of the tuff rock layers beneath the landfill and groundwater flow direction is affected, as well as the content of clay minerals in the bedrock around the landfill site (in the example of rock / soil only reach 54%, so the conservative anions such as chloride can still be move freely). Therefore, the selection of the location of landfills in the area Sarimukti is not good enough if it is not offset by the implementation of the system and monitoring the landfill